Codenames : duet [games] - Chvátil, Vlaada; Eaton, Scot; Kučerovský, Tomáš; Horálek, František; Murmak, Filip; Holt, Jason (Czech Games Edition, 2017)
Codenames duet keeps the basic elements of Codenames - give one-word clues to try to get someone to identify your agents among those on the table - but now you're working together as a team to find all of your agents. Your objective: to contact 15 agents while avoiding a band of enemy assassins.